Designing a Web-Based Employee Task Management Information System at CV Achai Berkat Sejahtera - Fadhlan Fakhrizal Fauzaini; Wasino Wasino; Tri Sutrisno (Publikasi Indonesia, 2024)
Designing a Web-based Employee Task Management Information System on CV. Achai Berkat Sejahtera is a plan made to assist business owners in employee management and help employees communicate an obstacle in an organized manner so that communication misses do not occur. Designing CV Employee Task Management Information System. Achai Berkat Sejahtera has features such as Employee Task Management Systems and a dashboard for admins to see employee performance. The design of this Information System uses the Waterfall System Development Life Cycle (SDLC) development methodology. The database that this application uses uses a MySQL database. The programming languages used are HTML, CSS, JS, and PHP with the Bootstrap Framework and CodeIgniter which produce attractive and dynamic web applications. With a dynamic web application, it will be able to help admins and employees in accessing and processing data.